Blue Public Expenditure Review : Guidance Note - World Bank (World Bank, Washington, DC, 2021)
This guidance note helps World Bank teams answer 6 key questions to help prepare a country’s blue public expenditure review (PER), a valuable tool for countries on their journey to a sustainable blue economy: (1) what is the scope of the review, (2) how much does the government spend and on what, (3) how much is spent now (adequacy) and what can be afforded in the medium and long term (sustainability), (4) are public resources being used efficiently and effectively, (5) is the public financial management system set up to enhance financial accountability, and (6) does public spending promote equity